2001
DOI: 10.1074/jbc.m103386200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Glycerol Phosphate Acyltransferase Directs the Incorporation of Exogenous Fatty Acids into Triacylglycerol

Abstract: The mitochondrial isoform of glycerol-3-phosphate acyltransferase (GPAT), the first step in glycerolipid synthesis, is up-regulated by insulin and by high carbohydrate feeding via SREBP-1c, suggesting that it plays a role in triacylglycerol synthesis. To test this hypothesis, we overexpressed mitochondrial GPAT in Chinese hamster ovary (CHO) cells. When GPAT was overexpressed 3.8-fold, triacylglycerol mass was 2.7-fold higher than in control cells. After incubation with trace [ 14 C]oleate (ϳ3 M), control cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 36 publications
2
72
1
Order By: Relevance
“…We (25) have shown that a 3.8-fold increase in mtGPAT1 activity in CHO cells increases TAG content 2.7-fold and [ 14 C]oleate incorporation into TAG 3.4-fold. Although that study strongly suggested that mtGPAT1 directs fatty acid toward TAG synthesis, CHO cells provide limited information because their oxidation rate is low and exogenous fatty acids are primarily metabolized to glycerolipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We (25) have shown that a 3.8-fold increase in mtGPAT1 activity in CHO cells increases TAG content 2.7-fold and [ 14 C]oleate incorporation into TAG 3.4-fold. Although that study strongly suggested that mtGPAT1 directs fatty acid toward TAG synthesis, CHO cells provide limited information because their oxidation rate is low and exogenous fatty acids are primarily metabolized to glycerolipids.…”
Section: Discussionmentioning
confidence: 99%
“…14 C]oleate incorporation into TAG 3.4-fold (25). In the Ad-GPAT1-infected hepatocytes, a 13-fold increase in GPAT activity resulted in 2.4-, 3-, and 2.4-fold increases in TAG mass at 100, 250, and 750 M oleate, respectively (Fig.…”
Section: Adenoviral Mediated Overexpression Of Mtgpat1 In Hepatocytesmentioning
confidence: 99%
“…This result was surprising for several reasons. First, expression of mitochondrial GPAT1 or the newly identified mitochondrial GPAT2 increases TG synthesis in cultured cells (14,28). Second, GPAT3 has been reported by others to increase triglyceride synthesis (14).…”
Section: Discussionmentioning
confidence: 99%
“…The role for mtGPAT in up-regulating TAG synthesis is also supported by studies of overexpressed rat mtGPAT in Chinese hamster ovary cells. Expression of recombinant rat mtGPAT in Chinese hamster ovary cells results in a 3.8-fold increase in NEM-resistant GPAT activity, a 4-fold increase in [ 14 C]oleate incorporation into TAG, and a 30% decrease in [ 14 C]oleate incorporation into phospholipids (10). To confirm the critical role of mtGPAT in the regulation of TAG synthesis, mtGPAT null mice were generated (8).…”
mentioning
confidence: 99%